Priming and temperature limits for germination of dispersal units of Urochloa brizantha (Stapf) Webster cv. basilisk - Nakao, E. A. [UNESP]; Cardoso, V. J. M. [UNESP] (Instituto Internacional de Ecologia, 2015)
The objective of this study was to evaluate the effect of priming treatments on the upper and lower thermal limits for germination of Urochloa brizantha cv. basilisk, and testing the hypothesis that pré-imbibition affect thermal parameters of the germination. Pre-imbibed seeds both in distilled water (0 MPa) and PEG 6000 solution (–0.5 MPa) were put to germinate in different temperatures. It is suggested that U. brizantha seeds have low response to priming when they were placed to germinate in medium where water is not limiting. The response of U. brizantha seeds to priming is dependent on the temperature and water potential conditions at which the seeds are pre-imbibed, as well as on the germination temperature. The optimum temperature for germination of U. brizantha shift toward warmer temperatures in primed seeds. Priming effect was more pronounced at temperatures closer to the upper and lower limit for germination, but probably that response cannot be accounted for changes in the thermal time constant (θT(g)) and ceiling temperature (Tc(g)). Otherwise, a decrease in the base temperature (Tb) was observed in primed seeds, suggesting that the Tb distribution in U. brizantha seeds is influenced by priming.

O objetivo deste estudo foi avaliar o efeito do tratamento pré-germinativo priming sobre os limites térmicos inferior e superior para a germinação de Urochloa brizantha cv. basilisk, e testar a hipótese de que a pré-embebição afeta os parâmetros térmicos da germinação. Sementes pré-embebidas, tanto em água destilada (0 MPa) quanto em solução de PEG 6000 (–0,5 MPa) foram colocadas para germinar em diferentes temperaturas. Os resultados sugerem que sementes de U. brizantha apresentam baixa resposta ao priming quando colocadas para germinar em meio onde a água não é limitante. A resposta de sementes de U. brizantha para o priming é dependente das condições de temperatura e potenciais hídricos em que as sementes são pré-embebidas, bem como para a temperatura de germinação. A temperatura ótima para germinação de sementes de U. brizantha altera-se para temperaturas mais altas em sementes pré-embebidas. O efeito de priming foi mais pronunciado em temperaturas mais próximas do limite superior e inferior para a germinação, mas, provavelmente essa resposta não foi responsável por mudanças na constante tempo térmico (θT(g)) e temperatura teto (Tc (g)). Por outro lado, uma diminuição na temperatura base (Tb) foi observada em sementes pré-embebidas, sugerindo que a distribuição Tb em sementes de U. brizantha é influenciada pelo priming.
Priming e temperaturas limites de germinação de unidades de dispersão de Urochloa brizantha (Stapf) Webster cv. basilisk
Keywords: Palisade grass; Osmoconditioning; Osmotic potential; Thermal time; Grama paliçada; Condicionamento osmótico; Potencial osmótico; Tempo térmico